2023
DOI: 10.1021/acs.jafc.3c06104
|View full text |Cite
|
Sign up to set email alerts
|

Plant miRNA bol-miR159 Regulates Gut Microbiota Composition in Mice: In Vivo Evidence of the Crosstalk between Plant miRNAs and Intestinal Microbes

Qin Xu,
Xinshu Qin,
Yi Zhang
et al.

Abstract: New evidence reveals that bol-miR159, an miRNA rich in fruits and vegetables, cross-kingdomly functions in mammalian bodies. However, whether the miRNA could regulate gut microbiota remains unclear. Here, the effect of miR159 on mouse intestinal microbes was comprehensively examined. The results showed that supplementation of miR159 to the chow diet significantly enhanced the diversity of mouse gut microbiota without causing pathological lesions or inflammatory responses on the intestines. At the phylum level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Previous studies found that miR159 could survive in vitro digestion and significantly increase the diversity and richness of mouse gut microbiota. 12,17 Given its high were first subjected to acclimatization of 3 days and subjected to gavage feeding of saline (CD group), miR2911 oligomer (miR2911 group), nucleotides of miR2911 (NT group), and heteroduplex of miR2911 (HDmiR group). The mice were given the gavage once a day for 7 days, anesthetized, and sacrificed on the eighth day.…”
Section: ■ Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies found that miR159 could survive in vitro digestion and significantly increase the diversity and richness of mouse gut microbiota. 12,17 Given its high were first subjected to acclimatization of 3 days and subjected to gavage feeding of saline (CD group), miR2911 oligomer (miR2911 group), nucleotides of miR2911 (NT group), and heteroduplex of miR2911 (HDmiR group). The mice were given the gavage once a day for 7 days, anesthetized, and sacrificed on the eighth day.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Previous studies found that miR159 could survive in vitro digestion and significantly increase the diversity and richness of mouse gut microbiota. , Given its high stability, we asked if miR2911 has a function of shaping the profile of intestinal microbes. The experiment scenario is shown in Figure A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations